Affiorano perle da queste pagine... Una nota sulla biblioteca di Massimo Fagioli come biblioteca d'autore - Gruppo di lavoro Biblioteca, Archivio e documentazione, Fondazione Massimo Fagioli (Il sogno della farfalla, 2024)
This contribution aims to provide an initial account of the cataloging, study and organization work being undertaken by the volunteers of the Library working Group (Archive and records, Massimo Fagioli Foundation), focused on the personal library of psychiatrist Massimo Fagioli. From these preliminary notes, the significance of this collection emerges clearly. Comprising volumes rich with annotations, personal notes and marginalia, the library offers invaluable insights into Fagioli’s intellectual and scientific work, as well as his broader conceptual developments. This collection is deeply interconnected with the psychiatrist’s personal archive, further enhancing its importance for understanding his scholarly output.